DESCRIPTION OF DIAGNOSTIC COVID-19 ADULT PATIENTS AT ROYAL PRIMA HOSPITAL - Fanny Maler; Wienaldi Wienaldi; Adrian Adrian (Jambura Journal of Health Sciences and Research, 2022)
Abstrak Coronavirus disease 2019 (COVID-19) adalah masalah kesehatan yang memiliki tipe virus baru yang sebelumnya tidak muncul pada manusia, yaitu virus pembawa COVID-19. Coronavirus merupakan sekelompok besar virus yang memicu kasus penyakit gejala ringan hingga parah. COVID-19 kali ini menjadi masalah paling serius di dunia. Jumlah kasusnya meningkat setiap hari dan seluruh individu terserang COVID-19 adalah dari semua usia dan jenis kelamin. Tujuan penelitian ini untuk mengetahui gambaran diagnostik pasien dewasa COVID-19 di RSU Royal Prima Medan dari bulan Oktober hingga Desember 2020 yang terdapat 164 orang. Penelitian dilakukan dengan metode deskriptif dan retrospektif. Penelitian ini mendeskripsikan gambaran diagnostik pasien dewasa Covid-19 di RSU Royal Prima berdasarkan sumber data sekunder dengan melihat usia, jenis kelamin, dan gejala yang paling sering dialami sesuai dengan data yang telah tercatat pada rekam medik di RSU Royal prima Medan, dilakukannya penelitian ini pada bulan Maret â€“ Juni 2021. Hasil dari penelitian ini menunjukan pasien COVID-19 terbanyak adalah pasien dengan jenis kelamin laki-laki berjumlah 93 orang (56,7%) serta gejala yang paling sering dialami secara umum dan berdasarkan jenis kelamin, yaitu demam, batuk, dan sesak nafas, serta lebih banyak terjadi pada usia 26-35 tahun. Kata kunci: COVID-19; Gejala; Jenis Kelamin; Usia Abstract Coronavirus disease 2019 (COVID-19) is a health problem with a new type virus that has never been occured before in humans, the virus that carries COVID-19, namely SARS-CoV-2. Corona virus is a large family of viruses that cause illness ranging from mild to severe symptoms. COVID-19 is currently the most serious problem in the worlds. The number of cases is increasing every day and the people who infected with COVID-19 were all ages and genders. The purpose of this study was to find out the diagnostic explanation of adult COVID- 19 patients at RSU Royal Prima Medan in October-December 2020 which contains 164 people. This study was conducted using a descriptive method and a retrospective approach. This research was explaining the diagnostic explanation in adult Covid-19 patients at the RSU Royal prima Medan, based on secondary data sources by looking at the ages, genders and the most frequently experienced symptoms according to data that has been recorded in the medical record at the RSU Royal prima Medan, this research was conducted in March â€“ June 2021. The results of this study showed that most of the COVID-19 patients were male that consist of 93 people (56,7%) and the most common symptoms and based on genders were fever, cough, shortness of breath, and more common at the age of 26-35 years.